Front and Back Matter for Volume 1 Issue 1, July 2024 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2024)
Volume 1, Issue 1, July 2024 This issue consists of 5 articles contributed by 23 authors affiliated with 13 affiliations from five countries including Indonesia (Universitas Airlangga, Universitas Hindu Indonesia, Indonesian Society of Epidemiologists, One Health Laboratory Network, Institut Teknologi Sepuluh Nopember, Universitas Padjadjaran, Universitas Pendidikan Ganesha, Sekolah Tinggi Ilmu Kesehatan Medistra Indonesia), United States (Universitas of Michigan), United Kingdom (University College London), Timor Leste (Serviçu Municipal da Saúde de Bobonaro), and Nigeria (University of Port Harcourt, Rivers State University).